2023
DOI: 10.1109/access.2023.3318724
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of a Low-Speed High-Torque-Density Direct-Drive External-Rotor PMSM for Belt Conveyor Application

Yongda Song,
Guangwei Liu,
Siyang Yu
et al.

Abstract: Aiming at the shortcomings of complex mechanical transmission structure and low efficiency of the existing belt conveyor driven by asynchronous motor, this paper focuses on the investigation of a new type of low-speed high-torque-density direct-drive permanent magnet synchronous motor (LHDPMSM) for driving the belt conveyor. The proposed LHDPMSM utilizes external rotor structure to achieve the goal of fully direct drive of the belt conveyor. First, the topology and advantages of the straight-shape externalroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[5] took the optimal pole-arc combination with the lowest cogging torque as the starting point and explored the feasibility of reducing cogging torque. [6] compared the differences between integer-slot and fractional-slot windings for an outer-rotor permanent magnet synchronous motor, and investigated the selection rules for pole-slot combinations. [7] compared and analyzed the performance of permanent magnet synchronous motors with different pole-slot ratios, providing results for torque ripple and cogging torque under various pole-slot combinations.…”
Section: Introductionmentioning
confidence: 99%
“…[5] took the optimal pole-arc combination with the lowest cogging torque as the starting point and explored the feasibility of reducing cogging torque. [6] compared the differences between integer-slot and fractional-slot windings for an outer-rotor permanent magnet synchronous motor, and investigated the selection rules for pole-slot combinations. [7] compared and analyzed the performance of permanent magnet synchronous motors with different pole-slot ratios, providing results for torque ripple and cogging torque under various pole-slot combinations.…”
Section: Introductionmentioning
confidence: 99%
“…The results show that the overall performance of the 32P132S true fractional slot is better. The harmonic distortion rate of the no-load back EMF of the motor under the three pole-slot ratios of 32P48S, 40P48S and 42P54S was compared, and it was found that the waveform of 40P48S was more sinusoidal [14]. However, it is not enough to compare the no-load back EMF only.…”
Section: Introductionmentioning
confidence: 99%